Ultrasensitive Detection of 2,4-D at Surface of a Hybrid Silica Nanoparticle Based on Photoinduced-Electron Transfer Enhanced Fluorescence - Gao, Daming; Sun, Hong; Si, Jingyu; Chen, Hong; Zhu, Dechun; Shi, Jianjun (Asian Journal of Chemistry, 2012)
This paper reports the ultrasensitive detection 2,4-D at the surface of hybrid silica nanoparticles through the enhanced-fluorescence intensity based on photoinduced-electon transfer mechanism. Nitrobenzoxadiazole (NBD) fluorophore and organic amine were covalently modified onto the surface of silica nanoparticles to form a hybrid monolayer of dye fluorophores and amine ligands. Photoinduced electron transfer (PET) between nitrobenzoxadiazole and free amine at the spatial approach occurred at the surface of hybrid silica nanoparticles and the fluorescence intensity showed a suitable decrease by comparison of the original intensity of ligands APTS-NBD formed between amine and nitrobenzoxadiazole. The presence of 2,4-D leads to fluorescence enhancement due to inhibition PET between amine and fluorophores. In addition, these nanoparticles can be developed into chips by assembling on arrays onto silicon wafer for detection of proton.